Pengaruh Ekstrak Daun Kemangi terhadap Penurunan Kadar Kreatinin dalam Darah Tikus Putih yang Diinduksi Parasetamol - Arianto Adi Wibowo; Endang Ediningsih; Samigun . (Nexus Kedokteran Translasional, 2012)
Background: Induced by parasetamol in large quantities will damaging in proximal tubule. Creatinine which should secreted by glomerolus will back in blood stream if occur kidney obstruction that which decreasing in-blood levels of creatinine. The purpose of this research is to find out whether the extract of kemangi has an effect to decrease in-blood levels of creatinine in white rats induced by parasetamol. Methods. The research was an experimental laboratoric study with the post test only controlled group design. This study was done in Setia Budi University. Subjects in this research were tirthty male white rats (Rattus norvegicus), 2-3 month of age and 150-220 gram of each weight. Subjects were divided into 5 groups.Group I as a negative control only received normal saline. Group II as a positive control and group III, IV, and V received parasetamol (150 mg/200 g body weight) every 3 day for 10 days. Group III received extract kemangi at 40mg / 200g body weight every 3 day for 10 days. Group IV received extract kemangi at 80mg / 200g body weight every 3 day for 10 days. Group V received extract kemangi at 120 mg 200 g body weight every 3 day for 10 days. Treatment were conducted on 11st after a 10-day adaptation. Blood sampling via plexus vena orbita of white rats for creatinine levels measured were conducted on 21st day. Then data was analyzed using One-Way ANOVA and LSD. Result. Result of One-Way ANOVA showed that there was a significant different between 5 groups: positive and negative control groups, and three dosages difference treatment (40mg, 80mg, 120mg / 200gr BB). Result of LSD showed that there was a significant different between positive control group and treatment groups; and between control group, but there was not the significant different between negative control group and treatment groups; and each treatment groups. Conclusion. All of the extract kemangi dosages has significantly effect to decrease in- blood levels of creatinine in white rats induced by parasetamol. Statisticaly, there is no significant different in the dose diffenrence at treatment 1, 2 and 3 (40mg, 80mg, 120mg / 200gr BB). Keywords: extract kemangi, decrease in-blood levels of creatinine, parasetamol.